Spatial and temporal variation in volatile composition suggests olfactory division of labor within the trap flowers of Aristolochia gigantea - Martin, Kyle R. (2017)
The olfactory components of floral advertisement can be complex, often showing dynamic patterns of emission and chemical composition that may reflect diverse functions related to pollination. In this study we investigated the spatial and temporal variation of volatile production in the distinctive kettle trap flowers of the Neotropical pipevine Aristolochia gigantea (Aristolochiaceae). These flowers show unusual complexity in scent chemistry and floral morphology in addition to conspicuous changes in scent at distinct stages during floral ontogeny. In this study, volatiles were collected from separate stages in development (bud, female, male, wilted flower), and from different functional units (limb, black ring, yellow disk, utricle, nectary) within each stage. Our results document a strikingly complex and dynamic floral scent composition for A. gigantea. Female stage floral emissions are dominated by sweet lemon-scented citronella-like compounds including (E)- and (Z)-citral, citronellol and citronellal, and at the same time include smaller amounts of pungent, brood-site associated volatiles such as dimethyl disulfide, 2-heptanone, and 3-methyl-1-butanol. Volatile emissions plummet one day later in male stage flowers, except for increased production of monoterpenoids and sesquiterpenoids, including a burst of linalool within the floral chamber. Volatiles emitted from wilted flowers resemble the vegetative background as soon as 48 h post anthesis. Multidimensional scaling revealed unexpected differentiation of volatile emissions across spatial units of the complex flower (e.g. within vs. outside of the trap), as well as at different stages of sexual expression as flowers matured. These results suggest that protogynous kettle trap flowers or inflorescences utilize a chemical division of labor, in concert with visual and tactile cues, to choreograph pollinator behavior such that female and male floral functions are optimized.